Prolonged Penile Erection in an Adolescent with Angelman Syndrome under Aripiperazole: A Case Report: Prolonged penile erection in Angelman syndrome - Hassanzadeh Rad, Afagh; aminzadeh, vahid (Iranian Journal of Child Neurology, 2025)
Angelman syndrome (AS) is a genetic neurodevelopmental disorder characterized by mental retardation, ataxia, and happy social behavior. Aripiprazole is an atypical antipsychotic drug used for treating irritability in patients with autism spectrum disorder in > 6-year-old children and adolescents. Notably, prolonged penile erection is an unknown complication of Aripiprazole. Therefore, the present case report aimed to present a unique prolonged penile erection in an adolescent with Angelman syndrome under Aripiprazole. In this case report, priapism occurred several hours after consuming 5 mg of Aripiprazole. Since he was neither a cigarette smoker nor an alcohol abuser, had no medical issues, and did not report any history of penile or perineal trauma, the urologist suggested that the priapism he experienced might be linked to the use of Aripiprazole. Fortunately, he recovered after stopping the medication. Generally, we mentioned controversial results from previous case reports on the effect of Aripiprazole. It is unknown why some case reports noted priapism post Aripiprazole use, and some mentioned priapism palliation by switching to this drug from other antipsychotics. While it seems that the tendency to priapism may be an idiosyncratic reaction or the α1-adrenergic receptors change or disorders in the predisposed patient, there is a need for further comprehensive studies on this issue